Effects Of Conservation Accounting And Tax Risk On Firm Value: Agency Costs As A Moderating Factor - Ady Lulus Setyawan; Herman Nur Yasin; Reskino Reskino (Universitas Muhammadiyah Malang, 2023)
Purpose: Finding out how tax risk, financial conservatism, and agency costs impact firm value is the objective of this research. Methodology/approach: To select 45 companies according to the criteria, we utilized the population of all businesses that are members of the Food and Staples, Beverage Retail Sub Sector. As part of the quantitative investigation, data analyzed using Partial Least Squares method. Findings: The results of the study show that tax risk and accounting conservatism both have a partial effect on company value, but agency costs have no effect on firm value, agency costs do not fully strengthen the relationship between tax risk and accounting conservatism on firm value, agency costs in research this gives rise to the influence of tax risk on firm value, but can also strengthen accounting conservatism on firm value. Practical implications: Previous research findings reveal that these elements have very little or no impact on business value; However, the findings of this research have become a strong controversy so that they can become a reference for external and internal companies in decision making. Originality/value: This novelty is agency costs as a moderator which can strengthen or weaken factors that influence firm value.